Application of Artificial Intelligence Technology in Coal Mine Mechanical and Electrical Equipment - Bai, Qingsong (Journal of Artificial Intelligence and Information, 2025)
This article explores the application of artificial intelligence technology in coal mine electromechanical equipment. Firstly, the definition and development history of artificial intelligence were outlined. Then, the advantages of its application in the coal mining industry were elaborated, including improving equipment operating efficiency, enhancing fault diagnosis capabilities, improving safety assurance levels, and optimizing equipment maintenance management. Specific applications include unmanned coal mining, coal mine safety monitoring, intelligent power supply, ventilation and belt conveyor systems, as well as mechanical and electrical equipment fault diagnosis and maintenance. Although there are still areas for improvement in the application, it is expected to promote the intelligent, efficient, and safe production of the coal mining industry in the future, which will contribute to energy security and economic development.